Management matters: the link between hospital organisation and quality of patient care. Issue 1 (1st March 2001) - West, Elizabeth
Abstract : Some hospital trusts and health authorities consistently outperform others on different dimensions of performance. Why? There is some evidence that "management matters", as well as the combined efforts of individual clinicians and teams. However, studies that have been conducted on the link between the organisation and management of services and quality of patient care can be criticised both theoretically and methodologically. A larger, and arguably more rigorous, body of work exists on the performance of firms in the private sector, often conducted within the disciplines of organisational behaviour or human resource management. Studies in these traditions have focused on the effects of decentralisation, participation, innovative work practices, and "complementarities" on outcome variables such as job satisfaction and performance. The aim of this paper is to identify a number of reviews and research traditions that might bring new ideas into future work on the determinants of hospital performance. Ideally, future research should be more theoretically informed and should use longitudinal rather than cross sectional research designs. The use of statistical methods such as multilevel modelling, which allow for the inclusion of variables at different levels of analysis, would enable estimation of the separate contribution that structure and process make to hospital outcomes.